Perilaku Masyarakat dalam Pelestarian Hutan Mangrove di Kabupaten Pangkep Provinsi Sulawesi Selatan - Zainudin, Zainudin; Sumardjo, Sumardjo; Susanto, Djoko (Jurnal Penyuluhan, 2015)
Mangrove forest is one natural resource which essential for the life of living creatures that lives on its surrounding. The existence of mangrove forests has become an integral part of the lives of coastal communities; hence the existence of mangrove forests should be maintained and preserved. Mangrove forest sustainability cannot be separated from the behavior of the people who live around that forest. The objective of this research was (1) to examine the behavior of the coastal communities conserving mangrove forests, (2) to examine the factors related to coastal communities’ behavior in managing and conserving mangrove forest. The populations were the 100 heads of fisherman households taken from Tekolabbua and Pundata Baji Village of Pangkep District. This research was correlational research. This data was analyzed using Spearman Rank correlation by using SPSS programming. The result shows that the behavior of coastal communities in the preservation Pangkep mangrove forests is in the middle level. Factors related to this are behavior is the intensity of extension activities and environmental support. Keywords: coastal community behavior, managing and conserving mangrove forests